The Price Elasticity of Hard Drugs: The Case of Opium in the Dutch East Indies, 1923-1938 - van Ours, Jan C. (Journal of Political Economy, 1995)
At the beginning of this century the Dutch government controlled the opium market in the Dutch East Indies–nowadays Indonesia–for several decades. This state monopoly was called the opiumregie. Using information gathered during the opiumregie, this paper estimates price elasticities of opium consumption. It appears that short-term price elasticities of opium use are about -0.7. Long-term price elasticities are about -1.0.